Smoking Behavior and the Incident of Osteoporosis in the Elderly: Meta-Analysis - Anasulfalah, Hakim; Verasita, Prissy; Widiyanto, Aris; Atmojo, Joko Tri (Indonesian Journal of Global Health Research, 2023)
Osteoporosis is a metabolic bone illness which involves bone density loss and micro destruction, enabling bone to develop into fragile, porous, and readily shattered. There are both controllable and non-modifiable risk variables for osteoporosis. Smoking, drinking behavior, and numerous other modifiable variables are examples. The goal of this research is to identify the possibility of osteoporosis among senior smokers. Research purposes to determine the influence of smoking behavior and the incidence of osteoporosis The following PICO criteria are used in this systematic review and meta-analysis investigation: Population: The elderly are the majority of the population. Intervention: smoking. Comparison: not smoking. Outcome: Osteoporosis. The articles used in this research were obtained from three databases: Google Scholar, Pubmed, and Science Direct. Keywords to search for articles are "Obesity" AND "Preeclampsia" AND Multivariate AND Pregnancy. Over 2013 and 2023, articles were utilized. To choose articles, the PRISMA flow diagram has been used. The papers were evaluated using the Review Manager 5.3 instrument. Seven cohort studies in the country of the United States (America), Europeans (Bosnia and Herzegovina), China, Iran, and Korea are among the countries in Asia that have been included in the systematic review and meta-analysis.. In accordance to the cohort study's forest plot results, elderly smokers have a 1.30 times greater risk of osteoporosis than elderly nonsmokers (aOR= 1.30; 95% CI= 0.81 to 2.08), and the results of this study are statistically significant (p <0.001).